Hubungan Tingkat Pendidikan dengan Status Demensia pada Lansia Berdasarkan Kajian Data Sekunder di Posbindu Caringin - Citra Windani Mambang Sari; Dicky Priyatno Tarigan; Imas Rafiyah (Jurnal Keperawatan Muhammadiyah, 2022)
Health problems in the elderly are characterized by a decrease in functional ability and adaptation which over time can cause dementia. The cause of dementia was important to know in order to reduce the incidence of dementia in the elderly. Knowing the status of dementia and its risk factors can be used as basic data in developing dementia prevention programs at the Puskesmas. This study aims to determine the relationship between education level and dementia status in the elderly who participate in Posbindu activities at Caringin Health Center. The design of this study was correlational with a retrospective approach, namely identifying secondary data on the relationship between education level and dementia status in the elderly in the Caringin Health Center working area with 125 elderly respondents. Data analysis in this study used a frequency distribution and Fisher's Exact. The results of this study showed that most of the respondents or about 84% had mild or normal dementia status. Chi Square test results with Fisher's Exact analysis. Obtained - value = 0.048 with a value of = <0.05, which means that there is a correlation between education level and dementia status in respondents in this study, which means that the higher the education level, the lower the chance of dementia. The implication of this research is the need for strategies that need to be carried out in optimizing the health of the elderly, especially the prevention of dementia and its management.